Upaya Peningkatan Keaktifan Belajar Siswa Kelas 4 Tema 8 Menggunakan Model Student Team Achievement Division - Suhariyadi, Suhariyadi; Eko, Sugeng; Suyoto, Suyoto (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2023)
This study aims to determine whether the STAD model can increase student activeness. This study used Classroom Action Research (PTK) which consisted of two cycles. Each cycle consists of two meetings. The subjects in the study were grade IV students of SDN Karanggedang totaling 11 students consisting of 9 boys and 2 girls. The data collection methods used were interviews, observation and documentation. STAD (Student Team Achievement Division) model". with stages 1) Conveying goals and motivation, 2) Group division, 3) Learning activities in teams, 4) Individual and group rewards, 5) Evaluation and conclusion. The application of the STAD (student team achievement division) model is very suitable to be applied in elementary schools. Based on observations about student activeness using the STAD (student team achievement division) model in the pre-cycle, the average percentage was 48.5%. Cycle I get a percentage of 57.9% and cycle II gets a percentage of 81.75%, so the STAD (student team achievement division) model is very well used to increase student activeness thus the research hypothesis is accepted. Based on observations from the implementation of cycle I learning gets an average percentage of 72.9%. In cycle II got an average score of 90.5%.